Effects of Transformational Leadership Style, School Climate, and Teacher Competence on Teacher Career Advancement in Jambi - Pratama, M Raditya Rizky; Sofwan, Muhammad; Habibi, Akhmad (FKIP Universitas Jambi, 2026)
Teacher career advancement is a core industry measure that sustains the stability of basic education teaching staff and drives improvements in regional teaching quality. The rationality of its evaluation mechanism directly shapes the long-term development momentum of faculty teams at private schools. At present, there is obvious ambiguity in the implementation of supporting policies for private junior high school teachers’ career advancement at the local level in Indonesia. A large number of private school teachers in the Jambi region cannot receive clear responses to their career advancement appeals, and there has long been a gap in local empirical research on the factors influencing this group’s career advancement. This study takes private junior high school teachers in the Jambi region as its sample, and uses quantitative empirical methods to explore the impact of three core categories of factors on teachers’ career advancement. The study confirms that all three categories of factors produce significant effects on career advancement outcomes. Based on these findings, it proposes an optimization plan that incorporates the three core categories of factors into a unified assessment framework. This conclusion can not only provide a practical basis for local faculty management, but also offer empirical support for improving private school faculty policies in other regions of Indonesia.